Perception of the ethical climate among healthcare professionals in an emergency room from southern Brazil. - Carpes Lanes, Taís; de Lima Dalmolin, Graziele; Maciel da Silva, Augusto; Antunez Villagran, Camila; da Silva Caram, Carolina; de Souza Magnago, Tânia Solange Bosi (Revista Cuidarte)
Introduction: The ethical climate is defined as the shared perception among healthcare professionals of what is ethically correct behavior and how to deal with ethical issues. Objective: To evaluate the perception of the ethical climate among health professionals working in an emergency room. Materials and Methods: Cross-sectional study carried out with healthcare professionals working in the emergency room of a university hospital in southern Brazil. Collection took place in January 2024 through the Positive Ethical Climate Promotion Platform, through the Hospital Ethical Climate Survey-Brazilian Version instrument. The data was organized and analyzed on the Positive Ethical Climate Promotion Platform, applying descriptive statistics. Results: 71 health professionals participated in the research, in which the general ethical climate was classified as positive (M=3.73; SD=0.60). The factors were evaluated as positive, except for the medical factor (M=3.23; SD=1.16), classified as negative. Descriptively, female professionals (p=0.063), with a partner (p=0.508), aged over 42 years (p=0.047) and with training time over 17 years (p=0.072) presented high averages for positive ethical climate, however, only age showed a significant association. Discussion: Despite the positive assessment of the general ethical climate, the importance of self-reflection and self-awareness when making ethical decisions in care is understood. Conclusion: The general ethical climate and its factors were evaluated as positive, however, the medical factor was perceived as negative.